2021
DOI: 10.1523/jneurosci.1397-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of Local and Cross-Area Interactions during Neuroprosthetic Learning

Abstract: How does the brain integrate signals with different timescales to drive purposeful actions? Brain-machine interfaces (BMIs) offer a powerful tool to causally test how distributed neural networks achieve specific neural patterns. During neuroprosthetic learning, actuator movements are causally linked to primary motor cortex (M1) neurons, i.e., “direct” neurons that project to the decoder and whose firing is required to successfully perform the task. However, it is unknown how such direct M1 neurons interact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…This, with other recent work, leads us to conclude that M1 task–relevant cells multiplex signals locally ( 11 , 44 ) as well as from distant-area cerebellar activity ( 62 ). Our regression of M1 BMI potent space activity also indicated that cerebellum TR i units showed a broader timescale influence of cerebellum on M1 TR d activity [this is different from the shorter timescale influences seen between M1 TR d and M1 TR i units ( 44 )]. Such broader influence of cerebellar activity may also be related to coordination in the larger motor network.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This, with other recent work, leads us to conclude that M1 task–relevant cells multiplex signals locally ( 11 , 44 ) as well as from distant-area cerebellar activity ( 62 ). Our regression of M1 BMI potent space activity also indicated that cerebellum TR i units showed a broader timescale influence of cerebellum on M1 TR d activity [this is different from the shorter timescale influences seen between M1 TR d and M1 TR i units ( 44 )]. Such broader influence of cerebellar activity may also be related to coordination in the larger motor network.…”
Section: Discussionsupporting
confidence: 82%
“…Upon a simple comparison of latency of M1 and cerebellar spiking activities’ peaks, we observed that cerebellum TR i activity tended to peak before M1 TR d during early trials [time to peak for M1 activity: 238.01 ± 6.42 ms; and time to peak for cerebellum activity: 236.82 ± 6.48 ms, mixed-effects model: t (646) = −0.07, P = 0.93] and late trials [time to peak for M1 activity: 239.82 ± 8.26 ms and time to peak for cerebellum activity: 211.16 ± 15.12 ms, mixed-effects model: t (646) = −1.87, P = 0.06]. This then lead us to develop a GLM to determine the relationship between cerebellum indirect activity and M1 activity ( 44 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation